2009
DOI: 10.1103/physrevb.79.054529
|View full text |Cite
|
Sign up to set email alerts
|

Impurity effects on the±s-wave state of the iron-based superconductors

Abstract: We studied the impurity scattering on the Ϯs-wave superconductor ͑SC͒, with realistic parameters for the Fe pnictide SCs. Using the T-matrix method, generalized for the two bands, we found that the strong scattering limit of impurities forms an off-centered resonance state inside the superconducting ͑SC͒ gap, which modifies, surprisingly, the density of states ͑DOS͒ of a fully opened gap to a V-shaped DOS as if in the case of a d-wave SC. This behavior provides coherent explanations to the several conflicting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
210
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(221 citation statements)
references
References 36 publications
9
210
1
Order By: Relevance
“…This coherence peak (Hebel-Slichter peak) [24,25] comes from the formation of superconducting gaps. The absence of the peak and a power-law behavior of T −1 1 at low temperatures indicate the occurrence of unconventional states [26][27][28].In this paper we claim that the bulk measurements of NMR rates detect a 3D odd-parity fully-gapped topological superconducting state in time-reversal-invariant multi-orbital systems. An inverse coherence effect just below T c is the signature of this odd-parity state; the coherence factor contributes to the NMR rates with an opposite sign to that of the conventional s-wave states.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…This coherence peak (Hebel-Slichter peak) [24,25] comes from the formation of superconducting gaps. The absence of the peak and a power-law behavior of T −1 1 at low temperatures indicate the occurrence of unconventional states [26][27][28].In this paper we claim that the bulk measurements of NMR rates detect a 3D odd-parity fully-gapped topological superconducting state in time-reversal-invariant multi-orbital systems. An inverse coherence effect just below T c is the signature of this odd-parity state; the coherence factor contributes to the NMR rates with an opposite sign to that of the conventional s-wave states.…”
mentioning
confidence: 83%
“…This coherence peak (Hebel-Slichter peak) [24,25] comes from the formation of superconducting gaps. The absence of the peak and a power-law behavior of T −1 1 at low temperatures indicate the occurrence of unconventional states [26][27][28].…”
mentioning
confidence: 99%
“…The correction to T c by the impurity scattering is a universal function of the impurity scattering rate Γ. For the s +− -wave superconductor, it was shown that the SC transition temperature is completely suppressed if the ratio between Γ and the T c value without impurities is approximately larger than 1 [36]. The value of Γ can be estimated from the resistivity difference ∆ρ i between the Li-deficient and stoichiometric Li 1−x FeAs via ∆ρ i = m * Γ/e 2 n, where m * is the effective mass of quasiparticle and n is the electron density per unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…2 For iron-based superconducting materials, the impurity effect in the SC state has also been theoretically studied intensively. [3][4][5][6][7][8][9][10] It was proposed that a single nonmagnetic impurity could be used to distinguish the pairing symmetry and the in-gap bound states could exist for the typical s ± pairing symmetry. [8][9][10] The in-gap bound states for s ± pairing should be different from those in cuprates due to the absence of quasiparticle excitations at low energy.…”
mentioning
confidence: 99%